2009
DOI: 10.1007/s00542-009-0817-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of flow induced vibration of head gimbal assembly

Abstract: The airflow of a 10,000 rpm hard disk drive is simulated using the LES turbulent model. The critical parameters for using LES model to get the correct/reliable result are discussed. The flow induced vibration of the head gimbal assembly is calculated with the obtained fluid force acting on the head gimbal assembly (HGA) and compared with measured results. Good agreement is observed between the measured and simulated results. The optimization of the airflow is further carried out to reduce the flow induced vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…They showed that reduction of the vibrations is related to the change of the airflow between disks. The effect of airflow on vibration of disk and arm has been reported [6]- [9]. The airflow in recent HDDs become more complicated because of aerodynamic parts, such as a spoiler and a bypass channel, introduced in HDDs for reducing FIV.…”
Section: Introductionmentioning
confidence: 98%
“…They showed that reduction of the vibrations is related to the change of the airflow between disks. The effect of airflow on vibration of disk and arm has been reported [6]- [9]. The airflow in recent HDDs become more complicated because of aerodynamic parts, such as a spoiler and a bypass channel, introduced in HDDs for reducing FIV.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, a weight-saving hole in the middle of the actuator arm induced a vortex structure which resonated with the mode of the HSA between 7 and 9 kHz. Zhang et al (2010) investigated an effect of a flow diverter upstream of the actuator arm and a spoiler downstream of the actuator arm. They performed numerical calculations with models of an original commercial drive, a drive with the flow diverter and a drive with the flow diverter and the spoiler.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation on the air-flow induced vibration of actuator arm fixed at the disk middle diameter between the two disks in a commercially available HDD operating at 10 000 rpm were carried out by our group [8], [9]. Two different cases viz.…”
Section: Introductionmentioning
confidence: 99%